Hollow Fiber Liquid-Phase Microextraction At-Line Coupled to Capillary Electrophoresis for Direct Analysis of Human Body Fluids - Miková, Blanka; Dvořák, Miloš; Ryšavá, Lenka; Kubáň, Pavel (Analytical chemistry, 2020)
A simple and cheap all-in-one concept for at-line coupling of hollow fiber liquid-phase microextraction (HF-LPME) to commercial capillary electrophoresis (CE) is demonstrated, which enables the direct analysis of complex samples. A disposable microextraction device compatible with injection systems of Agilent CE instruments is proposed, which consists of a short segment of a porous HF attached to a tapered polypropylene holder. The holder maintains a constant position of the HF in a CE vial during extraction and simultaneously guides the injection end of a separation capillary into the HF lumen for automated CE injection and analysis. In a typical analytical procedure, the HF is impregnated with a water-immiscible solvent, its lumen is filled with 5 μL of an aqueous acceptor solution, and the microextraction device is placed in a 2 mL glass CE vial containing 550 μL of a donor solution. The vial is agitated at 750 rpm for 10 min, and the resulting acceptor solution is injected directly from the HF lumen into the commercial CE. No additional manual handling is required, except for the transfer of the CE vial to the CE autosampler. Multiple complex samples can be simultaneously pretreated in a multiple-well plate format, thus significantly reducing the total analysis time. Suitability of the analytical method is demonstrated by the direct determination of model basic drugs (nortriptyline, haloperidol, loperamide, and papaverine) in physiological solutions, urine, and dried blood spot (DBS) samples. Repeatability of the method is better than 12.8% (%RSD), extraction recoveries range between 34 and 76%, and enrichment factors are 37-84. The method is linear in a range of 2 orders of magnitude (R2 ≥ 0.9977) with limits of detection of 0.7-1.55 μg/L. The method has a high potential for the direct analysis of DBS samples since DBS elution and HF-LPME are performed simultaneously during the 10 min agitation. The manual DBS handling is thus reduced to inserting the DBS punch into the CE vial only. Moreover, the universal character of the HF-LPME might extend the applicability of the method to a wide range of analytes/matrices, and combination with other commercial detectors might improve the selectivity/sensitivity of the CE analysis.
Keywords: mikroextrakce kapalné fáze; papaverin; Loperamide; Surface Properties; Liquid Phase Microextraction; Haloperidol; povrchové vlastnosti; loperamid; Body Fluids; Papaverine; velikost částic; lidé; tělesné tekutiny; poréznost; haloperidol; Particle Size; Nortriptyline; elektroforéza kapilární; Porosity; Electrophoresis, Capillary; nortriptylin; Humans